GeoGebra-assisted instructional strategies for developing the students’ mathematical communication skills: A systematic review in Indonesian high schools - Mutiara M. Ilyas; Irwan Akib; Muhammad Muzaini (Universitas Ahmad Dahlan, 2026)
This systematic review aims to identify, categorize, and evaluate the effectiveness of GeoGebra-assisted instructional strategies reported in various published studies in developing mathematical communication skills among Indonesian high school students. Specifically, the review seeks to: (1) identify and categorize the types of GeoGebra-assisted instructional strategies employed by Indonesian teachers; (2) synthesize evidence regarding their effectiveness on students' mathematical communication skills; and (3) analyze implementation challenges and facilitating factors within the Indonesian educational context. Following the PRISMA framework, the study analyzed 20 empirical articles published between 2024 and 2025 which met the preset criteria. The use of Geogebra in the three predominant instructional strategies, such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), and Discovery Learning, could enhance students' visual, symbolic, and verbal communication skills. The synthesis reveals that GeoGebra's interactive features facilitate mathematical representation and discourse, though implementation faces challenges including infrastructural limitations and varying levels of teacher readiness. Facilitating factors include GeoGebra's accessibility, visual capabilities, and compatibility with collaborative learning approaches. The novelty of this review lies in its focused synthesis of implementation dynamics within the Indonesian context. Practical implications underscore the need for targeted professional development and institutional support to optimize GeoGebra integration. This study contributes an evidence-based framework to guide educators and policymakers in fostering effective, communication-oriented mathematics instruction.